Beyond GDP. Measuring What Counts for Economic and Social Performance - M. D. Simonova (Vestnik MGIMO-Universiteta)
A review of Stieglitz J., Fitoussi J.-P., Duran M. Beyond GDP. Measuring Economic Development and Social Progress. OECD: Paris, 2018. 148 p.